Lineage specification in glioblastoma is regulated by METTL7B - Myrianni Constantinou; James Nicholson; Xinyu Zhang; Eleni Maniati; Sara Lucchini; Gabriel Rosser; Claire Vinel; Jun Wang; Yau Mun Lim; Sebastian Brandner; Sven Nelander; Sara Badodi; et al. (Cell Reports, 2024)
Summary: Glioblastomas are the most common malignant brain tumors in adults; they are highly aggressive and heterogeneous and show a high degree of plasticity. Here, we show that methyltransferase-like 7B (METTL7B) is an essential regulator of lineage specification in glioblastoma, with an impact on both tumor size and invasiveness. Single-cell transcriptomic analysis of these tumors and of cerebral organoids derived from expanded potential stem cells overexpressing METTL7B reveal a regulatory role for the gene in the neural stem cell-to-astrocyte differentiation trajectory. Mechanistically, METTL7B downregulates the expression of key neuronal differentiation players, including SALL2, via post-translational modifications of histone marks.